Public-Private Partnership in the Agriculture of Russia and the European Union: Economic Problems and Prospects for Development - KUZNETSOV, Nikolai Ivanovich; UKOLOVA, Nadezhda Viktorovna; MONAKHOV, Sergey Vladimirovich; SHIKHANOVA, Juliya Anatolyevna (Journal of Advanced Research in Law and Economics; Vol 8 No 8 (2017): JARLE, Volume VIII, Issue 8(30), Winter 2017DO - 10.14505//jarle.v8.8(30).18, 2018)
The authors of the article explore the specifics of the development of public-private partnership in the economy of Russia and the countries of the European Union. In the study, the authors identified the factors that affect the development of public-private partnerships in nowaday conditions. The authors’ interpretation of the concept of ‘public-private partnership’ is given in the article, the features of its use in agriculture are analyzed. The experience of development of public-private partnership in the EU countries and Russia is considered. The study presents extensive statistical material that characterizes the level of PPP development in the EU and Russia. The successful experience of using the PPP mechanism in the Russian agriculture is presented. The authors outline the priorities for the development of public-private partnership in Russia and the EU. The conclusion is made about the need for active development of PPP in the agriculture of Russia, the development directions in the EU are defined.